2010
DOI: 10.1159/000317032
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal Tremor: Co-Occurrence with Other Movement Disorders

Abstract: Introduction: Limited epidemiologic information exists regarding the co-occurrence of laryngeal tremor (LT) and tremor in other parts of the body, and of other movement disorders. Tremor is the involuntary skeletal muscle contraction that leads to oscillatory movement. It can affect many parts of the body including the chin, neck, laryngeal muscles, or limbs. When it is not associated with parkinsonism, it is called an essential tremor. We reviewed our 5-year experience with LT patients and the presence of oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…There is a growing belief that isolated head tremor and other focal or task-specific tremors are dystonia [14••]. Consequently, both the TRIG and the MDS Consensus criteria for classic ET exclude isolated position-specific or task-specific tremors (eg, occupational tremors, primary writing tremor) and isolated tremor in the voice [44], tongue, and chin [45] or legs [34••, 46]. …”
Section: Introductionmentioning
confidence: 99%
“…There is a growing belief that isolated head tremor and other focal or task-specific tremors are dystonia [14••]. Consequently, both the TRIG and the MDS Consensus criteria for classic ET exclude isolated position-specific or task-specific tremors (eg, occupational tremors, primary writing tremor) and isolated tremor in the voice [44], tongue, and chin [45] or legs [34••, 46]. …”
Section: Introductionmentioning
confidence: 99%
“…3,4 Essential tremor is one of the most common movement disorders, affecting approximately 4-5.6% of people over the age of 40 years. 5 Essential tremor is characterized by a postural and action tremor with a frequency of 4-12 Hz that typically involves the upper extremities.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown 5% to 20% and 32.3% to 93% prevalence of coprevalent movement disorders at presentation in patients with ADSD and vocal tremor. In the present study, patients with ADSD were found to have significantly fewer concomitant movement disorders (11.5%) compared to patients with ADSD + LT (38.7%) or LT (57.1%).…”
Section: Discussionmentioning
confidence: 92%